START TO PLAY TENNIS LIKE INCETIVE TO DEVELOPMENT SPORTS IN MONTENEGRO - Dimitrije Rašović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
At the end of 19 centuries tenis like popular game has srarted to play in Vojvodina. At 1880 tennis grassy courts was built in Senta and from that year it started to play in Vojvodina. Austrohungarion officers propageted tennis who were built tennis courts in their barracks but they was built courts in city parks. At 1892 the first tennis competition organised which mean that the first clubs probably had establishment befor thet year. Later at 1894 tennis started to play at palace of greand duke Nikola in Cetinje. Later tennis started to play in srbia at 1900. At that year people organised the first tennis tournament in vrsac. Momcilo Tapavica the first sout slovenion who was montegrion descent who was participat at first modern olimpic's games in atina at 1896 he gave great countrabucsion developeted tennis sport in Montenegro. Momcilo Tapavica come to palase of graund duke's Nikola at 1902 and ofter thet date his all family moved to Herceg-Novi and they spent all time to secound world war. At first olimpic's games Momcilo Tapavica took parr in these sports/tennis, life weights, wrestling. Certain thet like talented sportman he gave great contabution not only in tennis than he gave contribution in the other sports in Montenegro.